Changing profile of bacterial infection and microbiome in cystic fibrosis: when to use antibiotics in the era of CFTR-modulator therapy - Justyna Milczewska; Zulfiya Syunyaeva; Aleksandra Żabińska-Jaroń; Dorota Sands; Stephanie Thee (European Respiratory Review)
The advent of cystic fibrosis transmembrane conductance regulator (CFTR) modulator therapy, especially the triple therapy combining the drugs elexacaftor, tezacaftor, ivacaftor (ETI), has significantly changed the course of the disease in people with cystic fibrosis (pwCF). ETI, which is approved for the majority (80–90%) of pwCF, partially restores CFTR channel function, resulting in improved mucociliary clearance and, consequently, improved lung function, respiratory symptoms and pulmonary exacerbations. The bacterial burden of classical CF pathogens such as Pseudomonas aeruginosa and Staphylococcus aureus is reduced without reaching eradication in the majority of infected patients. Limited data is available on less common or emerging bacterial pathogens. ETI has a positive effect on the lung microbiome but does not fully restore it to a healthy state. Due to the significant reduction in sputum production under ETI, respiratory samples such as deep-throat swabs are commonly taken, despite their inadequate representation of lower respiratory tract pathogens. Currently, there are still unanswered questions related to this new therapy, such as the clinical impact of infection with cystic fibrosis (CF) pathogens, the value of molecular diagnostic tests, the durability of the effects on respiratory infection and the role of fungal and viral infections. This article reviews the changes in bacterial lung infections and the microbiome in CF to provide evidence for the use of antibiotics in the era of ETI.